Cytoskeletal microdifferentiation: A mechanism for organizing morphological plasticity in dendrites - Kaech, Stefanie (The National Academy of Sciences, 2001)
Experimental evidence suggests that microfilaments and microtubules play contrasting roles in regulating the balance between motility and stability in neuronal structures. Actin-containing microfilaments are associated with structural plasticity, both during development when their dynamic activity drives the exploratory activity of growth cones and after circuit formation when the actin-rich dendritic spines of excitatory synapses retain a capacity for rapid changes in morphology. By contrast, microtubules predominate in axonal and dendritic processes, which appear to be morphologically relatively more stable. To compare the cytoplasmic distributions and dynamics of microfilaments and microtubules we made time-lapse recordings of actin or the microtubule-associated protein 2 tagged with green fluorescent protein in neurons growing in dispersed culture or in tissue slices from transgenic mice. The results complement existing evidence indicating that the high concentrations of actin present in dendritic spines is a specialization for morphological plasticity. By contrast, microtubule-associated protein 2 is limited to the shafts of dendrites where time-lapse recordings show little evidence for dynamic activity. A parallel exists between the partitioning of microfilaments and microtubules in motile and stable domains of growing processes during development and between dendrite shafts and spines at excitatory synapses in established neuronal circuits. These data thus suggest a mechanism, conserved through development and adulthood, in which the differential dynamics of actin and microtubules determine the plasticity of neuronal structures.